Assessment of mutagenic potential of Cordillera Administrative Region (CAR) atmospheric particulate matter using a novel mutagenicity assay - Cristobal, Edgar Q., Jr.; David, Kamille Anne V. (2014., 2014)
Mutagenicity tests are used to determine substances that have the potential to alter living organism's genetic material. This paper aimed to produce a novel mutagenicity assay using Serratia marcescens 1748. In this qualitative assay, mutation was induced on the red-pigmented Serratia marcescens bacteria by using selected established mutagens which resulted to loss pigmentation. The efficiency of this novel mutagenicity assay using Serratia marcescens 1748 was compared to a widely used toxicity assay called Ames Test using Salmonella typhimurium TA 102 and TA 104 by means of positive (toluene, ethidium bromide, sodium azide and ethyl methylsulfonate) and negative (sterile water) controls. The mutagenicity ratio (MR) was obtained by dividing the number of induced revertants or mutants by the spontaneous revertants or mutants. Results from two-way ANOVA showed that the novel mutagenicity assay was not significantly different from Ames test and can therefore be used as an alternative in mutagenicity testing. The two assays were also used to detect possible mutagens in Cordillera Administrative Region (CAR) rural and urban atmospheric particulate matter (APM). At present, this study is pioneer in detecting mutagenicity activitiy in air in the Philippines. It was concluded that CAR rural and urban APM is not mutagenic in Ames test but tested positive in the proposed microbial assay. Its positive response on the novel mutagenicity test can be accounted from the different components of atmospheric particulate matter that could have disrupted prodigiosin biosynthesis in Serratia marcescens -- Author's abstract.
Thesis (Bachelor of Sciencein Biology) -- University of the Philippines Philippines, 2014.
Includes bibliographical references (leaves 60-65).
Keywords: Mutagenicity testing -- Philippines -- Cordillera Administrative Region